Reconstructing the Catholic Church and Restituting the Power of the Sovereign: The Clergy in the Composite Monarchy of the Habsburgs during the Seventeenth Century - Marie-Élizabeth Ducreux (L'Atelier du CRH, 2020)
Can Catholic clergy be considered as a social, political, and even pastoral category, reconstructed within certain historical and historiographical circumstances, outside of its ecclesiological definition? Are the clergy a body or a social group whose overarching identity would erase differences of situations and constraints? The present article explores this avenue in the framework of the composite monarchy of the Habsburgs in seventeenth-century Central Europe. It will take into account the scales of interactions and conflicts between actors and structures. It will also draw attention to the effects of the clergy’s double-allegiance to the Catholic Church and to a local political body. In each land composing this monarchy, then, the question arises of the existence of a category that is also a border, constitutional or statutory, that historians and jurists readily perceive as stable: that of the political representation of the clergy as a body. At the end of the fifteenth or at the beginning of the sixteenth century, all the lands over which the younger branch of the Habsburgs were to find themselves reigning, from 1526 on, possessed their own diet, each with its own dynamics and particularities, with its own history. As practices and rules differed, this clergy of a composite monarchy is therefore taken here as a transversal object, indissociably linked to local settings in which its members’ possibilities of action lay.